2022
DOI: 10.1021/jacs.2c02076
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Polyphosphazene Nanospheres Boosting Long-Lived Organic Room-Temperature Phosphorescence

Abstract: Long-lived organic room-temperature phosphorescence (RTP) has sparked intense explorations, owing to the outstanding optical performance and exceptional applications. Because triplet excitons in organic RTP experience multifarious relaxation processes resulting from their high sensitivity, spin multiplicity, inevitable nonradiative decay, and external quenchers, boosting RTP performance by the modulated triplet-exciton behavior is challenging. Herein, we report that cross-linked polyphosphazene nanospheres can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 169 publications
(85 citation statements)
references
References 46 publications
0
85
0
Order By: Relevance
“…[8][9][10] In general, RTP is difficult to achieve at room temperature due to the spin prohibition of triplet exciton transitions and the fact that triplet excitons are easily quenched by oxygen and other nonradiative processes. [11][12][13] Researchers would achieve RTP by the following methods: (1) doping rare earth metal ions or heteroatoms into the phosphors to facilitate intersystem crossing (ISC) processes; (2) embedding phosphors into rigid substrates, such as polymers, ionic crystals, amorphous materials, and macrocyclic molecules to suppress vibration and rotation; and (3) selecting rigid precursors and using self-assembly to regulate molecular stacking patterns, restricting nonradiative processes and protecting triplet excitons. [14][15][16][17] Over the past decade, researchers have made a steady stream of breakthroughs in the preparation of RTP materials, targeting mainly inorganic complexes or metal-free organic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] In general, RTP is difficult to achieve at room temperature due to the spin prohibition of triplet exciton transitions and the fact that triplet excitons are easily quenched by oxygen and other nonradiative processes. [11][12][13] Researchers would achieve RTP by the following methods: (1) doping rare earth metal ions or heteroatoms into the phosphors to facilitate intersystem crossing (ISC) processes; (2) embedding phosphors into rigid substrates, such as polymers, ionic crystals, amorphous materials, and macrocyclic molecules to suppress vibration and rotation; and (3) selecting rigid precursors and using self-assembly to regulate molecular stacking patterns, restricting nonradiative processes and protecting triplet excitons. [14][15][16][17] Over the past decade, researchers have made a steady stream of breakthroughs in the preparation of RTP materials, targeting mainly inorganic complexes or metal-free organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Although inorganic RTP materials with prolonged light emission are actively being sought for many applications including optoelectronic devices, photocatalysis, and emergency signage, 4–7 they are less suitable for applications such as anticounterfeiting and bioimaging materials, where bright, subsecond afterglow is required 8–10 . In general, RTP is difficult to achieve at room temperature due to the spin prohibition of triplet exciton transitions and the fact that triplet excitons are easily quenched by oxygen and other nonradiative processes 11–13 . Researchers would achieve RTP by the following methods: (1) doping rare earth metal ions or heteroatoms into the phosphors to facilitate intersystem crossing (ISC) processes; (2) embedding phosphors into rigid substrates, such as polymers, ionic crystals, amorphous materials, and macrocyclic molecules to suppress vibration and rotation; and (3) selecting rigid precursors and using self‐assembly to regulate molecular stacking patterns, restricting nonradiative processes and protecting triplet excitons 14–17 .…”
Section: Introductionmentioning
confidence: 99%
“…The efficient RTP property mainly benefited from the rigid polymer environment that restricted thermal decay channels of triplet excitons. Subsequently, the covalent-bonding-dominated RTP polymer systems have been developed rapidly through, for example, radical binary copolymerization, click chemistry, and covalent cross-linking reaction strategies. , In particular, intelligent RTP copolymers with color-tunable, UV-irradiation-activated, humidity-responsive, or circularly polarized luminescence (CPL)-active properties have attracted considerable attention.…”
Section: Covalent Bonding Rtp Polymer Systemsmentioning
confidence: 99%
“…Subsequently, the covalent-bonding-dominated RTP polymer systems have been developed rapidly through, for example, radical binary copolymerization, 21 click chemistry, 38 and covalent cross-linking reaction strategies. 39,40 In particular, intelligent RTP copolymers with color-tunable, UV-irradiationactivated, humidity-responsive, or circularly polarized luminescence (CPL)-active properties have attracted considerable attention. Inspired by the construction of multicolor RTP-doped polymer systems with diverse aggregates based on noncovalent interactions, we proposed a similar strategy to conjugate multiple long-lived RTP emitting centers onto a polymer backbone, enabling excitation-dependent, color-tunable copolymers without phase separation.…”
Section: Covalent Bonding Rtp Polymer Systemsmentioning
confidence: 99%
“…Organic room temperature phosphorescence (RTP) materials with a long afterglow property have unique advantages in anticounterfeiting, biological diagnosis and treatment, and optoelectronic devices. Intersystem crossing (ISC) of excitons and stable triplet excitons are prerequisites for organic materials to exhibit phosphorescence. Early organic RTP materials were mainly single-component compounds; the researchers increased the ISC ability of excitons by introducing carbonyl groups or halogen atoms into the molecules or designing donor–acceptor type molecular configurations. , As an emerging technology in recent years, people have found that guest–host doped strategy can cause the doped materials to have RTP activity, which has attracted widespread attention. The host matrix can help the energy transfer of guest excitons, and the rigid structure of the host can effectively limit the motion of the guests, thereby stabilizing the triplet excitons. However, despite the rapid development of doped RTP materials, these systems are basically two-component systems, which are often limited by low performance and limited functionality.…”
mentioning
confidence: 99%